Aerobic Dance: Facilities for the Development of Physical Education and Recreational Sports - Latuheru, Ricardo Valentino; Arfanda, Poppy Elisano (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study is an explanation based on a literature review about aerobic dance which is currently being favored by almost all Indonesian people. This literature review is quoted from Google Scholar, Science Direct, and books, using the keywords aerobic exercise, physical activity, dance aerobics, and recreational sports. The references are used from 2015 to 2022. Aerobic dance is a fun sport for an active lifestyle and is an indicator of future health. Aerobic dance is popular for several reasons, one of which is that it is low cost and can be performed anytime, anywhere, and by anyone regardless of gender and age. Aerobic dance can have a positive effect on physical and mental health. Aerobic dance can reduce risk factors for cardiovascular disease in all age groups, especially in the elderly, and reduce mental health problems such as lowering levels of reactions to stress, depression, and anxiety. Aerobic dance that is done regularly can improve physical and mental health. In addition, it has a positive impact on social relationships and increases self-efficacy. Aerobic dance is recommended as a recreational sport.